The structure of district schemes of the ecological network schemes north of Donetsk region - Блакберн, А. А. (Man and Environment. Issues of Neoecology)
The comparative characteristics of the area of the ecological network schemes north of Donetsk region. Emphasizes the principles of non-conformity of the environmental network of national and regional and local levels, based on the natural division of the territory – the national level, and administrative – regional and local levels. Obtained ballroom assess the diversity of ecological network at the district level, which allows us to compare the structural components of regional ecological networks and environmental networks themselves in terms of priority of their introduction into the general scheme of the ecological network of the country.